2014
DOI: 10.1185/03007995.2014.936932
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the quality of communication from nephrologists to primary care practitioners: a literature review

Abstract: There is some evidence that improving the quality of letters from specialists to PCPs may benefit patient care. This review suggests a need for research on communication from nephrologists about patients who have received care at a renal unit regardless of whether or not the patient continues to attend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Three reviews [161163] ( n  = 44 studies) of moderate- to high-quality evaluated communication as an intervention reporting inconclusive results. One review [161] uniquely assessed whether patients benefit from improved communication between primary healthcare practitioners and nephrologists.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three reviews [161163] ( n  = 44 studies) of moderate- to high-quality evaluated communication as an intervention reporting inconclusive results. One review [161] uniquely assessed whether patients benefit from improved communication between primary healthcare practitioners and nephrologists.…”
Section: Resultsmentioning
confidence: 99%
“…One review [161] uniquely assessed whether patients benefit from improved communication between primary healthcare practitioners and nephrologists. The review found little evidence of benefit from enhancing the quality of letters from specialists to primary healthcare practitioners.…”
Section: Resultsmentioning
confidence: 99%
“…This body of work largely consists of studies of the extent and consequences of late referral [ 7 ] and of enablers and barriers to collaboration [ 21 22 23 ]. Few studies test coordinated care interventions aimed explicitly at bridging primary care and nephrology via shared care models that go beyond the use of one-way consult letters or notes [ 24 25 26 ].…”
Section: Introductionmentioning
confidence: 99%